Development and Analysis of GIS Regional Political Profiles in West Java Utilizing the Spatial Overlay Join Method - Septiana, Egi; Rahman, Aedah Binti Abd; Manaf, Khaerul (CV. Generasi Intelektual Digital, 2024)
This research aims to build Geographic Information System (GIS) of Political Region Profiles in West Java using the Overlay Spatial Join method. The study addresses the political complexity in Indonesia, particularly in West Java, which serves as a significant political base. The success of political campaigns requires a profound understanding of voter preferences, demographic dynamics, and local issues. Limited access to accurate location data poses a serious obstacle to the effective design of campaign strategies. This research responds to these challenges by designing a GIS that integrates political and spatial data. The research focuses on West Java, where regional diversity poses unique challenges. Through the Overlay Spatial Join method, the research aims to provide in-depth insights into political region profiles, serving as a foundation for intelligent political campaign strategies. The benefits of the research include an understanding of regional characteristics, performance comparisons of political parties, and in-depth analysis for campaign resource efficiency. The system integrates data from various sources, provides spatial visualization, and enables the analysis of regional profiles for the identification of deep political information. The research's contribution is not only academic but also practical in enhancing the effectiveness of democracy and general elections in West Java.